Kinetic barriers to α-synuclein protofilament formation and conversion into mature fibrils. Issue 56 (28th June 2018) - Brown, James W. P.; Meisl, Georg; Knowles, Tuomas P. J.; Buell, Alexander K.; Dobson, Christopher M.; Galvagnion, Céline
Abstract : An increase in temperature allows the conversion of α-synuclein lipid-induced proto-fibrils to mature fibrils by overcoming the associated energy barrier. Abstract : Oligomeric and protofibrillar aggregates that are populated along the pathway of amyloid fibril formation appear generally to be more toxic than the mature fibrillar state. In particular, α-synuclein, the protein associated with Parkinson's disease, forms kinetically trapped protofibrils in the presence of lipid vesicles. Here, we show that lipid-induced α-synuclein protofibrils can convert rapidly to mature fibrils at higher temperatures. Furthermore, we find that β-synuclein, generally considered less aggregation prone than α-synuclein, forms protofibrils at higher temperatures. These findings highlight the importance of energy barriers in controlling the de novo formation and conversion of amyloid fibrils.